Listening to God and the Founding of the Law: Notes on Exodus 32.19–20. Issue 52 (2nd October 2021) - Benjamin, Andrew
ABSTRACT: The aim of this paper is to contribute to the development of a political theology that take both God and law as central. Rather than operate abstractly, the paper works closely on passages from Exodus and Genesis that are themselves linked directly to what is at stake in "listening to God". The transformation of the immediacy of listening to the necessarily mediated response to the law is the move that the passages from the Torah entail. Within that setting, listening breaks the hold of immediacy and thus the possibility of any immediacy of reception. What is opened as a result, the argument continues, is an importantly different hermeneutic register and philosophical anthropology.